Different Breeding Values Under Uniform Environmental Condition for Milk Production Yield Traits in Holstein-Friesian Cows - László Bognár; Zsolt Jenő Kőrösi; István Anton; Szabolcs Bene; Ferenc Szabó (Animals)
In this study, 1,616,549 Holstein-Friesian females were genotyped for genomic evaluation of genetic merit (BVGenomic). Genotyping was performed using the EuroGenomics MD v3.0 chipset on the Illumina microarray scanner platform operated by an accredited Illumina laboratory. In addition, international and national reference populations were used for traditional BLUP breeding value (BV) estimation for both individuals (BVBLUP) and parents (BVPedigree). A single-step BLUP animal model was used for this estimation. A sample of 190 first lactation progeny cows from a single herd, reared and kept under consistent environmental conditions, was used to validate the three types of BV estimation methods. Correlation and regression analysis were used to study the association between the phenotypic performance and the results of three different estimation models. The average production of the 305-day standard lactation was 10,910.5 kg milk, 397.86 kg butterfat and 365.33 kg protein. Comparative analyses showed that BVBLUP had the highest accuracy, followed by BVGenomic, while BVPedigree was the least reliable, R2 = 0.37 to 0.48; 0.09 to 0.23; 0.02 to 0.06, respectively.